Citraan dalam Novel Dua Garis Biru Karya Lucia Priandarini dan Gina S. Noer - Tikasari, Devi; Rahayu, Sri (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2023)
This research aims to identify and analyze the various forms of imagery used in the work and how these images influence the reading experience and understanding of the storyline. The author's interest in this novel stems from the authors' ability to depict the story with simple yet captivating language. The use of imagery in this work is a key factor in creating the atmosphere and understanding the characters and events in the story. The results of the analysis show that the imagery in this novel includes the portrayal of character behavior, character experiences, character conditions, the story's atmosphere, and the events that unfold within the narrative. Various forms of imagery, such as visual imagery, auditory imagery, movement imagery, tactile imagery, and olfactory imagery, are used to create a profound and captivating reading experience. Visual imagery helps describe the characters and the story's settings, while auditory imagery aids in comprehending the plot. Movement imagery depicts how characters move, while tactile and olfactory imagery explore the characters' sensory experiences. This research provides valuable insights into how authors utilize imagery to create a compelling reading experience and blend various elements in the story.